Management Education in European Countries - Svenson, Arthur L. (Academy of Management Journal, 1960)
Examines varied approaches to management education in Western Europe. Overview of university activities at Ghent, Belgium; Operations of the Netherlands Institute of Management; Speed of the movement for management education.